Testing Contrast Agents to Improve Micro Computerized Tomography (μCT) for Spatial Location of Organic Matter and Biological Material in Soil - Lammel, Daniel R.; Arlt, Tobias; Manke, Ingo; Rillig, Matthias C. (Frontiers in Environmental Science, 2019)
Soil carbon is essential for soil and ecosystem functioning. Its turnover and storage in soil are multifaceted processes that involve microbial activity in complex physical matrices. Biological litter, which include plants, animals and microorganisms, is decomposed in soil stimulating soil biota (archaea, bacteria, fungi, protists and animals) activity and yielding soil organic matter (SOM). Such decomposition processes are influenced by local physico-chemical characteristics including the spatial distribution of aggregates and pores. More refined analytical tools are needed to better understand these processes, especially considering the spatial 3D structure of soil matrices. Using synchrotron radiation (X-ray) micro computerized tomography (SR-µCT), we tested different contrast agents (staining methods) based on silver (Ag), eosin (Br based) and liquid and gaseous iodine (I) in order to spatially image biological material and SOM in soil samples. We also performed K-edge SR-µCT for the Ag and I2 treatments and conventional µCT for additional soil samples applying the I2 treatment. Our results indicated that I2 was the most efficient contrast method for SR-µCT imaging of soil samples. I2 qualitatively improved the images, but mainly, by using the K-edge SR-µCT, this method provided a powerful tool to determine the spatial location of SOM. We acknowledge that the use of SR-µCT is an expensive technique to study soil samples, which comes with bottlenecks in terms of access to facilities and measurement time. Nevertheless, we show that the I2 treatment improved soil images also using standard µCT. In conventional µCT the I2 treatment improved the visualization of biological material and consequently improved the qualitative analysis of fine plants roots and micro-fauna (Collembola). This improvement may have a positive implication in soil biology, by improving a non-destructive method to detect fungi (SR-µCT), soil fauna (conventional µCT) and roots in undisturbed soil samples. An unexpected finding was that the I2 treatment also stained the plastic sample containers (nylon and polyimide), indicating the potential for the I2 staining procedure to be applied for the detection of plastic pollution in soil samples.